Bifunctional Al2O3/polyacrylonitrile membrane to suppress the growth of lithium dendrites and shuttling of polysulfides in lithium-sulfur batteries. (1st October 2022) - Guo, Pengqian; Jiang, Pengfeng; Chen, Weixin; Qian, Guoyu; He, Deyan; Lu, Xia
Highlights: A bifunctional Al2 O3 /PAN nanofiber membrane is synthesized via a facile and robust manufacture process and low cost as well. The Al2 O3 /PAN membrane with 3D cross-linked structures can physically block the Z-directional Li dendrite growth through tortuous pores and multilayered structures. The Al2 O3 /PAN decorated by Al2 O3 nanoparticles demonstrates strong chemical interactions to trap the long-chain LiPSs, which efficiently confines the sulfur species in the cathode region and thus suppresses the shuttle effect. The resultant symmetric Li||Li cells and LSBs with Al2 O3 /PAN separator exhibit the outstanding mechanical/electrochemical performance. A reversible capacity of 2.08 mAh cm −2 is reached at 500 mA g −1 even under the sulfur loading of 3.6 mg cm −2 . Abstract: Interfacial engineering plays an important role in dynamically stabilizing the electrochemical performance of lithium-sulfur batteries (LSBs). Constructing a robust interface, e.g., using a multifunctional membrane, benefits not only for the suppression of lithium polysulfides (LiPSs) shuttling, but also for the inhibition of uncontrollable Li dendrite growth. Herein, a bifunctional membrane is fabricated with the Al2 O3 nanoparticle-embedded polyacrylonitrile nanofibers (Al2 O3 /PAN) in a facile way as separator, which are found effective in blocking the growth of Li dendrite and the shuttling of LiPSs in LSBs. The exposed Al2 O3 nanoparticles work in a responsible way to physiochemically capture the LiPSs and simultaneously let the Li ions shuttle through the PAN nanofiber network as the simulation indicated. The 3D cross-linked membrane can also block the oriented Li deposition and growth to make the symmetric Li||Li cell cycle over 1500 h without short circuit at 0.5 mA cm −2 . Moreover, the LSB exhibits a reversible capacity of 2.08 mAh cm −2 at 500 mA g −1 under the sulfur loading of 3.6 mg cm −2 . These results provide a doable and economy way to fabricate the robust membrane to deal effectively with the tough issues, which sheds new light on the design and optimization of high-energy-density sulfur prevailed rechargeable batteries. Graphical abstract: A bifunctional Al2 O3 /polyacrylonitrile nanofiber membrane is synthesized via a simple electrospinning method, as a highly efficient separator to regulate the lithium interfacial engineering and suppress the shuttle effect in lithium-sulfur batteries. The 3D cross-linked structures physically block the Z-directional lithium dendrite growth while the Al2 O3 nanoclusters inhibit the shuttling of polysulfides, which contribute to the outstanding electrochemical performance of lithium-sulfur batteries. Image, graphical abstract